Generation of whole genome bisulfite sequencing libraries from very low DNA input - Weichenhan, Dieter; Imbusch, Charles; Wang, Qi; Brors, Benedikt; Plass, Christoph (Lymphoma, 2019)
DNA methylation changes are dynamic processes which occur at cytosines of CpG dinucleotides and contribute to normal development but also to diseases. DNA methylation changes are most effective in promoters and enhancers, the former frequently being CpG-rich and the latter, in contrast, CpG-poor. Many genome-wide methods for DNA methylation analysis interrogate predominantly CpG-rich regions and, hence, spare enhancers and other potentially important genomic regions. Whole genome bisulfite sequencing (WGBS), in contrast, analyzes the DNA methylome in its entirety. Standard tagmentation-based whole genome bisulfite sequencing (TWGBS) is a Tn5 transposon-based method which requires only 30 ng of human input DNA and, hence, is particularly suited for precious biological samples like cells sorted by flow cytometry or laser capture microdissected tissue specimens. In the standard version, tagmentation generates DNA fragments flanked by uniform sequencing adapters. In a subsequent step, the non-covalently bound adapter oligonucleotide needs to be replaced by a novel oligonucleotide to provide the proper adapter sequence for the reverse strand in paired-end sequencing. The presented protocol describes an improved, simplified version of TWGBS where the inefficient oligo-replacement is circumvented by usage of a sequencing-compatible transposase-adapter complex. Consequently, genomic DNA of only a few hundred human cells is required to interrogate the complete human DNA methylome.
Gesehen am 23.04.2020